Efekk Atmosphere, Experience Marketing dan Food Quality terhadap Kepuasan Konsumen dan Minat Pembelian Ulang pada Konsumen Rasa Bunda - Derian Ottoman; Yolanda Soedibyo; Yanuar Dananjaya (Journal of Management and Bussines (JOMB), 2024)
This research aims to determine and analyze Atmosphere, Marketing Experience and Food Quality which have a significant effect on Consumer Satisfaction and Repurchase Interest in Rasa Bunda. The research method used in this research is a quantitative method. The total sample was 190 respondents with the sampling technique being snowball sampling as the sample collection technique. The data analysis technique uses multiple linear regression analysis. The research results show that atmosphere has an effect on consumer satisfaction at Rasa Bunda, experience marketing has a significant and positive effect on consumer satisfaction at Rasa Bunda, food quality has a significant effect on consumer satisfaction at Rasa Bunda, consumer satisfaction has no influence on repurchase interest at Rasa Bunda. atmosphere has no influence on repurchase interest in Rasa Bunda, experience marketing has no significant influence on repurchase interest in Rasa Bunda and food quality has a significant influence on repurchase interest in Rasa Bunda. In conclusion, improving various atmospheres, marketing experience and food quality can increase the level of satisfaction and buying interest. Keyword: Atmosphere, Experience Marketing and Food Quality, Customer Satisfaction